Rationalization of building micro-dams equipped with fish passages in West African savannas - Yangyuoru, M.; Unami, K.; Alam, A.H.M.B. (Journal of Stochastic Environmental Research and Risk Assessment (SERRA), 2010)
Micro-dams in West African savannas are investigated in conjunction with aquatic fauna and human activities at a community level. A study area is chosen in the Northern Region of Ghana. The micro-dams in the study area serve as habitats for fish, providing food and job opportunities for inhabitants, but their construction has sacrificed rice fields and fragmented migration routes of fish. A stochastic population dynamics model is developed to rigorously assess the effect of establishing fish passages between the fragmented habitats containing the microdams on the ichthyological fauna. Values of the model parameters are estimated from the literature and results of field surveys, in which ten fish species including cichlidae, clariidae, bagridae, schilbeidae, cyprinidae, and alistidae are reported to be present. A sustainability criterion is proposed to judge whether a set of model parameters realizes stationarity of the stochastic process representing the population dynamics. It is suggested that ichthyological fauna can be sustainable provided that the fishing activity is restricted to upstream migrating and fast growing species. More generally, building micro-dams in West African savannas will be much better justified when the dams are equipped with appropriately designed fish passages.
Keywords: Micro-dam; Aquatic fauna; Stochastic population dynamics model; Fish passage; Sustainability; Ghana